Measuring environmental innovation using patent data - Haščič, Ivan (OECD Environment Working Papers, 2015)
This paper refines indicators to measure innovation in environment-related technologies, drawing on recent methodological advances that allow a more accurate assessment of environment-related innovation in a broader range of countries and covering a greater variety of the relevant technologies. Three indicators are discussed in the paper: an indicator of technology development (a measure of inventive activity) in over 80 specific environmental technologies; an indicator of international collaboration in technology development (a measure of co-invention); and an indicator of technology diffusion (a measure of market protection). These indicators provide a range of tools for assessing innovative performance in country and policy studies. The indicators are based on patent data because they have a number of attractive properties compared to other alternatives: they are widely available, quantitative, commensurable, output-oriented and capable of being disaggregated - an important advantage when analysing environmental technologies. At the same time, not all innovations or inventions are patented, and measuring the number of patents by itself does not provide an indication of their relative importance and impact. Techniques have been developed to overcome these limitations, yet it is important to carefully interpret patent-based indicators